Waiting for in-Lab Polysomnography May Unnecessarily Prolong Treatment Start in Patients with Moderate or Severe OSA at Home Sleep Apnea Testing - Pordzik J; Seifen C; Ludwig K; Ruckes C; Huppertz T; Matthias C; Gouveris H (Nature and Science of Sleep)
Johannes Pordzik,1 Christopher Seifen,1 Katharina Ludwig,1 Christian Ruckes,2 Tilman Huppertz,1 Christoph Matthias,1 Haralampos Gouveris1 1Department of Otolaryngology, Head and Neck Surgery & Sleep Medicine Center, University Medical Center Mainz, Mainz, 55131, Germany; 2Interdisciplinary Center for Clinical Trials (IZKS), University Medical Center Mainz, Mainz, 55131, GermanyCorrespondence: Johannes Pordzik, Department of Otolaryngology, Head and Neck Surgery & Sleep Medicine Center, University Medical Center Mainz, Mainz, 55131, Germany, Email johannes.pordzik@unimedizin-mainz.dePurpose: The gold standard in obstructive sleep apnea (OSA) diagnostics is nocturnal full-night polysomnography (PSG). Due to high costs and high time effort portable respiratory polygraphy (PG or home sleep apnea testing-HSAT) has been developed. In contrast to PG the PSG gains relevant further information concerning sleep stages, arousals and leg movements. However, the role of PG in the diagnostic of OSA remains largely undefined. The aim of this study was to investigate the difference of PG- and PSG- related metrics in OSA, to understand if there is a difference in PG and PSG-based treatment decision and show up the time between performed PG and PSG.Patients and Methods: 99 consecutive patients with existing outpatient performed PG and followed PSG in our tertiary care otorhinolaryngology department between February 2020 and December 2023 were retrospectively assessed. All patients were treatment-naive at the time of consultation. The time between performed outpatient PG and PSG was calculated. Furthermore, clinical baseline parameter and PG as well as PSG data were evaluated. All data were then blinded presented with relevant comorbid diseases to two experts in sleep medicine in our tertiary care centre to decide whether PAP therapy was indicated or not.Results: Mean AHI was significantly higher in PSG (32.32 ± 22.78/h) compared to PG (22.60 ± 15.12/h) (p< 0.001). Mean duration between performed PG and PSG was 194.99 ± 131.96 days (range between 37 and 842 days). Only in two patients PAP-therapy was indicated with PG results but not with PSG results. Only in one case PAP-therapy was not indicated with PG results but with PSG results.Conclusion: These data suggest initiating OSA therapy based on PG results for patients with at least moderate OSA on PG, followed by a confirming PSG and a control PSG under treatment to avoid unnecessary prolongation of treatment start.Keywords: obstructive sleep apnea, portable respiratory polygraphy, polysomnography, PAP